Day of injury assessment of sport-related concussion. Issue 5 (11th March 2013) - McCrea, Michael; Iverson, Grant L; Echemendia, Ruben J; Makdissi, Michael; Raftery, Martin
Abstract : Objective: To conduct a critical review of the literature on instruments currently used in the assessment of sport-related concussion on the day of injury. Data sources: Computerised searches of the literature posted to MEDLINE, PubMed, CINAHL, PsychInfo and Cochrane Library from 1 January 1982 through 21 August 2012. Key words and medical embedded subheadings (MeSH) terms relevant to sport-related concussion were applied, which identified 577 articles. Study selection: In addition to MeSH term and key word criteria, a study was included in the analysis if the article: (1) was published in English, (2) represented original research, (3) pertained to sport-related concussion (ie, not non-sports traumatic brain injury), (4) included assessment or diagnostic data collected within 24 h of the injury event and (5) involved human research. A total of 41 studies qualified for review. Data extraction: All articles were examined to determine if the study met the additional requirements for inclusion. A standardised method was used to document critical elements of the study design, population, tests employed and key findings. Data synthesis: A large number of studies were analysed that reported data from testing conducted within 24 h of injury. These studies collectively demonstrated that a number of instruments are capable of measuring the acute effects of concussion across several domains, such as symptoms, cognition and balance. Results: Relating to specific assessment domains are compiled in separate tables and an interpretive summary of the findings is provided. Conclusions: Several well-validated tests are appropriate for use in the assessment of acute concussion in the competitive sporting environment. These tests provide important data on the symptoms and functional impairments that clinicians can incorporate into their diagnostic formulation, but they should not solely be used to diagnose concussion.